Determinants of COVID-19 vaccine preference: A survey study in Japan - Keisuke Kawata; Masaki Nakabayashi (Elsevier, 2021)
Objective: Vaccination is a critical measure for containing the COVID-19 pandemic. We survey the determinants that affect the preference for COVID-19 vaccines in Japan, a vaccine hesitant nation. Setting and design: We conducted a randomized conjoint analysis survey of the preference for vaccines on the Internet by recruiting a nonprobability sample of 15,000 Japanese adults. The survey assigned 5 choice tasks to the respondents. In each task, the respondents evaluated 2 hypothetical COVID-19 vaccines and were asked which they would choose. The vaccine attributes included efficacy, major and minor adverse side effects, country of vaccine development and clinical trial, and vaccine type. Treatment: The choice task asked the participants to select a vaccine from 2 hypothetical vaccines as an optional vaccine or select a vaccine as mandated one with a probability of 0.5 for each. Results: Compared to China-developed vaccines, domestically developed or US-developed vaccines raised the choice probability by 37.3 and 27.4 percentage points, respectively. A domestic clinical trial increased the choice probability by 14.8, an increase in efficacy from 50% to 90% increased that by 18.0, and a decrease in the risk of severe adverse side effects from 1 per 10 thousand to 1 per 1 million increased that by 16.9 percentage points, respectively. The vaccine type was irrelevant. Making vaccination compulsory increased the choice probability of China- and Russia-developed vaccines by 0.6 and 0.4, high-risk vaccines by 0.5, and a modestly effective (70%) vaccine by 0.4 percentage points, respectively. General vaccination hesitancy, political positions, demographic characteristics, education, and income were irrelevant. Conclusions: A domestically developed vaccine with a domestic clinical trial could substantially increase the preference for the vaccine. Making vaccination compulsory could modestly reduce the penalty for a vaccine with adverse side effects, geopolitical, and efficacy concerns, possibly through mitigating free-riding concerns to achieve herd immunity.